Coherent exciton-biexciton dynamics in GaN - Kyhm, K; Taylor, R; Ryan, J; Aoki, T; Kuwata-Gonokami, M; Beaumont, B; Gibart, P (2002)
Spectrally resolved and time-integrated four-wave mixing are used to measure the polarization dependence of biexcitonic signals and quantum beats between two-A-exciton (XAXAZ*) and A-biexciton (XAXA) states in a high-quality GaN epilayer. Mixed beats with two periods are observed: the first beating period corresponds to the energy splitting between XAXA*and XAXA; the second period corresponds to beating between A excitons (XA) and donor bound excitons (DOX). We also measure the polarization-dependent B-biexciton (XBXB) signal. The effective masses for the A and B holes are deduced from the binding energy.